Jaminan Konsumsi Halal pada Jual Beli Ayam Potong di Pasar Lakessi Kota Parepare - Pangestu, Dian Resky; Addury, Multazam Mansyur; GH, Nur Hishaly (Fakultas Syariah dan Hukum Islam Institut Agama Islam Negeri (IAIN) Parepare, 2022)
The purpose of this study was to examine the relationships between Slaughter Understanding (halal consumption guarantee) and Purchase Interest (buying and selling) of chicken pieces at Lakessi Market, Parepare City. The research method used in this research is mixed methods, namely by combining two form sofresearch, namely quantitative and qualitative research. The number of samples that will be used as part of this research is 100 people. The result of there search is that there is no significant influence on the level of understanding of slaughtering on the interest in buying chicken pieces at Lakessi Market, Parepare City. There were 12 respondents who questioned the process of slaughtering animals at Lakessi Market, Parepare City, but not in detail. This is because consumers fully entrust the slaughtering process to chicken traders.